Vitamin D status, vitamin D receptor polymorphisms, and risk of cardiometabolic multimorbidity - Jianhua Ma; Pingan Li; Jinqi Wang; Haiping Zhang; Zhiwei Li; Lixin Tao; Xinghua Yang; Yanxia Luo; Xiuhua Guo; Bo Gao (Nutrition Journal)
Abstract Background The prevalence of cardiometabolic multimorbidity (CMM) has increased substantially in recent years. Previous studies have established the associations between vitamin D, vitamin D receptor (VDR) polymorphisms, and the risk of individual cardiometabolic disease (CMD). However, the role of these factors in the progression of CMD to CMM or mortality remains unclear. This study aimed to investigate the associations between vitamin D, VDR polymorphisms, and the dynamic progression of CMM, as well as to explore the potential modification effect of VDR polymorphisms. Methods Data for this cohort study were extracted from the UK Biobank. CMM was defined as the coexistence of at least two CMDs, including type 2 diabetes (T2D), coronary heart disease (CHD), and stroke. A multi-state model was used to analyze associations between serum 25(OH)D, VDR polymorphisms and the dynamic progression of CMM. Results The sample included 396,192 participants. Over a median follow-up of 13.8 years, 55,772 individuals experienced at least one CMD and 28,624 died. Compared to participants with 25(OH)D < 25 nmol/L, those with 25(OH)D ≥ 75 nmol/L had HRs of 0.70 (95% CI, 0.67, 0.72) for baseline to first CMD (FCMD), 0.74 (95% CI, 0.67, 0.82) for FCMD to CMM, 0.66 (95% CI, 0.62, 0.70) for baseline to death, 0.84 (95% CI, 0.77, 0.92) for FCMD to death, and 0.85 (95% CI, 0.70, 1.03) for CMM to death. L-shaped relationships of these associations were noted, with a threshold around 45 nmol/L. The rs1544410 (BsmI) T alleles may have a detrimental effect, while the rs11568820 (Cdx2) T alleles may exert a protective effect in the early stages of CMM progression. Additionally, VDR polymorphisms significantly modified the association between serum 25(OH)D and certain stages of CMM progression. Conclusions Maintaining adequate vitamin D levels, as a readily implementable intervention strategy, not only reduces the risk of initial CMD but also delays the progression to CMM or death. Risk stratification based on VDR polymorphisms provides further insights for developing personalized prevention strategies.